Innovating a Writing Group for Female Cancer Patients: A Counselling Field Description - Larsen, Denise J.; Cumming, C; Hundleby, M.; Kuiken, D. (Canadian Journal of Counselling and Psychotherapy, 2007)
The effects of a cancer diagnosis can be devastating and far-reaching. Expressive-supportive group therapy has proven useful for treating patients struggling with many of these effects. In addition, individual therapeutic writing methods have shown benefit for many individuals addressing a variety of difficult life circumstances including cancer. In this article, we describe specific techniques and processes of an innovative expressive journaling group for cancer patients offered at a comprehensive cancer centre in western Canada. Further, we discuss existential and constructivist connections to our clients' experiences and our work. In addition, we note specific practice considerations and references. Finally, implications for research into journal writing groups are provided.